Tissue Metabolism, Hematotoxicity, and Hepatotoxicity of Trichlorfon in Carassius auratus gibelio After a Single Oral Administration - Lu, Jianfei; Zhang, Minli; Lu, Liqun (Frontiers in Physiology, 2018)
Trichlorfon is a most widely used organophosphate insecticide in aquaculture, many successful results have been reported for bath treatments of trichlorfon to control parasites. However, immersion treatments of large stocks with trichlorfon has caused serious environmental pollution. In contrast, oral administration treatment has advantages on reducing environmental pollution and having little effect in non-targeted species. The aim of this study was to investigate the effect of trichlorfon on Carassius auratus gibelio physiology after a single oral administration. In this study, Carassius auratus gibelio was subjected to oral gavage with various concentrations of trichlorfon (0.5 g/kg, 1 g/kg, and 2 g/kg). The trichlorfon concentration in the plasma and liver tissue was quantiﬁed using liquid chromatography-tandem mass spectrometry at different time points. At the beginning of oral exposure, the uptake of trichlorfon in the plasma and liver tissue was fast, and trichlorfon was rapidly eliminated to a low level within 24 h. In addition, acetylcholinesterase, superoxide dismutase, catalase and glutathione-S-transferase activities in the plasma and liver tissue changed signiﬁcantly after trichlorfon exposure. Additionally, vacuolar degeneration, necrosis, and congestion of the central vein were observed in the liver after trichlorfon exposure, as assessed by hematoxylin and eosin staining. Our results suggested that trichlorfon could accumulate and induce hematotoxicity and hepatotoxicity in the plasma and liver tissue, the toxicity induced by trichlorfon might result in physiological disturbances in ﬁsh.